2019
DOI: 10.1038/s41598-019-52252-z
|View full text |Cite
|
Sign up to set email alerts
|

Optical and magneto-optical properties of GdxFe(100-x) thin films close to the compensation point

Abstract: Unlike ferromagnetic materials, ferrimagnetic metals have recently received considerable attention due to their bulk perpendicular magnetic anisotropy, low net magnetization and tunable magnetic properties. This makes them perfect candidates for the research of recently discovered spin-torque related phenomena. Among other ferrimagnetic metals, GdFe has an advantage in relatively large magnetic moments in both sublattices and tunability of compensation point above the room temperature by small changes in its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Here, the thicknesses of the (Mn 4 N)B and capping layers and the dielectric constants of (Mn 4 N)B (ε (Mn4N)B ) were the fitting parameters. Because the resistivity of (Mn 4 N)B films is conductive [37], ε (Mn4N)B is given by the Drude-Lorentz model [12,14,15,38],…”
Section: Measurement Of Full-dielectric Tensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, the thicknesses of the (Mn 4 N)B and capping layers and the dielectric constants of (Mn 4 N)B (ε (Mn4N)B ) were the fitting parameters. Because the resistivity of (Mn 4 N)B films is conductive [37], ε (Mn4N)B is given by the Drude-Lorentz model [12,14,15,38],…”
Section: Measurement Of Full-dielectric Tensorsmentioning
confidence: 99%
“…Therefore, we analyzed samples with Al and Ta capping layers using the multi-sample analysis (MSA) mode to determine more accurate dielectric constants [41,42]. MSA allows us to fit ε (Mn4N)B by fixing the dielectric constant of the capping layer [14,43]. To verify the thicknesses of each layer obtained from SE, x-ray reflectivity (XRR) measurements were also performed at ambient temperature.…”
Section: Measurement Of Full-dielectric Tensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, it is also frequently used for spintronics research; to observe domain wall motion in magnetic nanowires, to evaluate spin Hall effect in heavy metals, and to detect spin-orbit torque in magnetic layer/heavy metal layer heterostructures [10][11][12][13]. We can also evaluate the off-diagonal part of permittivity, which is the magneto-optical properties that determine the magnitude of the magneto-optical effect, from MOKE measurement [14][15][16][17][18][19]. In the study of the magneto-optical Kerr spectrum of Co/Pt multilayer films, it is often reported that a very large Kerr rotation angle can be obtained in the ultraviolet region.…”
Section: Introductionmentioning
confidence: 99%